Integral transform with the extended generalized Mittag‐Leffler function - Kilbas, A. A.; Koroleva, A. A. (Mathematical Modelling and Analysis, 2006)
The paper is devoted to the study of the integral transformcontaining the special function å((á, â) n ;z) generalizing the Mittag‐Leffler type function in the space Â£v,r (1 ≤ r ≤ 8, í ∈ R) of Lebesgue measurable functions on R+ = (0,+8) such that ‖ƒ‖ v,r < 8, whereMapping properties such as the boundedness, the range, the representation and the inversion of the considered transform are proved. The results are based on the representation of the considered transform as the H‐transform.First Published Online: 14 Oct 2010